Reduced immunity to measles in adults with major depressive disorder. Issue 2 (19th March 2018) - Ford, Bart N.; Yolken, Robert H.; Dickerson, Faith B.; Teague, T. Kent; Irwin, Michael R.; Paulus, Martin P.; Savitz, Jonathan
Abstract: Background: Depression can impair the immunogenicity of vaccine administration in adults. Whereas many vaccinations are administered in childhood, it is not known whether adolescent or adult onset depression is associated with impairments in the maintenance of protection of childhood vaccines. This study tested the hypothesis that individuals with adolescent or adult onset mood disorders would display compromised immunity to measles, a target of childhood vaccination. Methods: IgG antibodies to measles were quantified using a solid phase immunoassay in volunteers with bipolar disorder (BD, n = 64, mean age of onset = 16.6 ± 5.6), currently depressed individuals with major depressive disorder (cMDD, n = 85, mean age of onset = 17.9 ± 7.0), remitted individuals with a history of MDD (rMDD, n = 82, mean age of onset = 19.2 ± 8.6), and non-depressed comparison controls (HC, n = 202), all born after the introduction of the measles vaccine in the USA in 1963. Results: Relative to HC, both the cMDD group ( p = 0.021, adjusted odds ratios (OR) = 0.47, confidence interval (CI) = 0.24–0.90), and the rMDD group ( p = 0.038, adjusted OR = 0.50, CI = 0.26–0.97) were less likely to test seropositive for measles. Compared with unmedicated MDD participants, currently medicated MDD participants had a longer lifetime duration of illness and were less likely to test seropositive for measles. Conclusions: Individuals with adolescent or adult onset MDD are less likely to test seropositive for measles. Because lower IgG titers are associated with increased risk of measles infection, MDD may increase the risk and severity of infection possibly because of impaired maintenance of vaccine-related protection from measles.